Structure-based feeding strategies: A key component of child nutrition. (1st July 2017) - Taylor, Maija B.; Emley, Elizabeth; Pratt, Mercedes; Musher-Eizenman, Dara R.
Abstract: Objective: This study examined the relationship between structure, autonomy promotion, and control feeding strategies and parent-reported child diet. Participants: Participants ( N = 497) were parents of children ages 2.5 to 7.5 recruited from Amazon Mechanical Turk. This sample was a Caucasian (79%), educated sample (61% college graduates) with most reports from mothers (76%). Methods and measures: Online survey including measures of parent feeding strategies and child dietary intake. Results: Use of structure-based feeding strategies explained 21% of the variance in child consumption of added sugar, 12% of the variance in child intake of added sugar from sugar-sweetened beverages, and 16% of the variance in child consumption of fruits and vegetables. Higher unhealthy food availability and permissive feeding uniquely predicted higher child added sugar intake and child consumption of added sugar from sugar-sweetened beverages. Greater healthy food availability uniquely predicted higher child fruit and vegetable intake. Conclusions: and Future Directions: In Caucasian educated families, structure-based feeding strategies appear to be a relatively stronger correlate of parent-reported child intake of added sugar and fruits and vegetables as compared to autonomy promotion and control feeding strategies. Longitudinal research may be needed in order to reveal the relationships between autonomy promotion and control feeding strategies with child diet. If future studies have similar findings to this study's results, researchers may want to focus more heavily on investigating the impact of teaching parents stimulus-control techniques and feeding-related assertiveness skills on child dietary intake.